ЗАСТОСУВАННЯ ЧАСТОТНО-ФАЗОВОГО МЕТОДУ ДЛЯ КОНТРОЛЮ ГЕОМЕТРИЧНИХ ПАРАМЕТРІВ ОБ’ЄКТІВ - Брагинець, І.О.; Кононенко, О.Г.; Масюренко, Ю.О. (Інститут електродинаміки НАН України, Київ, 2017)
Authors considered the possibility of using laser frequency-phase ranging systems in the radar mode for evaluating the quality and shape of the controlled diffuse-reflecting surfaces. We carried out analytical studies of the output value of frequency-phase systems for non-uniformity of controlled surfaces. The spectrum of the system output signal is estimated in this case and the amplitudes of the individual components of the spectrum are determined, the values of which characterize surface state or its profile. References 10, figures 2.